Electrode mixture, electrode, and battery
Patent Information
- Application Number
- CN202580021441.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-26
- Publication Date
- 2026-10-20
AI Technical Summary
[0027]根据本发明,提供一种电极合剂,其包含被碳被覆的电极活性物质和具有羧基的偏氟乙烯共聚物,初始粘度低,且操作性良好。而且,还提供使用该电极合剂得到的电极和电池。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to electrode mixtures, electrodes, and batteries. Background Technology
[0002] In the formation of the electrode composite layer of a non-aqueous electrolyte secondary battery, an electrode composite containing an adhesive (binder) and an active material is typically used. As the adhesive (binder), vinylidene fluoride polymers are primarily used. For the adhesive, high adhesion is required because it helps to bond the active material to the current collector. For example, Patent Document 1 describes introducing functional groups such as carboxyl groups into a fluorinated resin to improve adhesion to current collectors and improve solubility in solvents. Patent Document 2 describes an adhesive composition containing a copolymer of vinylidene fluoride and a compound with a specific structure (vinylidene fluoride copolymer), and describes that this vinylidene fluoride copolymer exhibits high adhesion to the current collector.
[0003] On the other hand, with the aim of reducing battery costs, the use of lithium iron phosphate (LFP) as the positive electrode active material is being studied. Furthermore, the use of lithium iron manganese phosphate (LFMP) as the positive electrode active material is also being investigated as a next-generation material.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 6-172452
[0007] Patent Document 2: Japanese Patent No. 5797206 Summary of the Invention
[0008] The problem that the invention aims to solve
[0009] To improve adhesion to current collectors, etc., it was considered to use the vinylidene fluoride copolymer described in Patent Documents 1 and 2 as an electrode binder in electrode mixtures (slurries) containing lithium iron phosphate (LFP) and lithium iron manganese phosphate (LFMP). However, when LFP and LFMP are mixed with the vinylidene fluoride copolymer, which has high adhesion strength to current collectors, the initial viscosity of the electrode mixture increases, and the thixotropy tends to increase. Moreover, electrode fabrication is very difficult with such electrode mixtures. After in-depth research, the inventors believe that the reason for the increased initial viscosity and thixotropy in electrode mixtures containing LFP and LFMP is that the carbon coating present on the surface of LFP and LFMP interacts with the carboxyl-containing vinylidene fluoride copolymer.
[0010] The present invention was made in view of the above-mentioned problems. The object of the present invention is to provide an electrode mixture comprising a carbon-coated electrode active material and a carboxyl-containing vinylidene fluoride copolymer, exhibiting low initial viscosity and good operability. Furthermore, the object is to provide electrodes and batteries obtained using this electrode mixture.
[0011] Solution for solving the problem
[0012] [1] The present invention provides an electrode compound comprising: a vinylidene fluoride copolymer having structural units derived from vinylidene fluoride and structural units derived from a vinyl compound having a carboxyl group; and a carbon-coated electrode active material, wherein the amount of carbon coating of the electrode active material is 0.5% by mass or more and 3.0% by mass or less relative to the mass of the electrode active material, the weight-average molecular weight Mwa of the vinylidene fluoride copolymer is 50,000 or more, and when the vinylidene fluoride copolymer is modified with a labeling substance composed of 1-bromomethylpyrene, and the weight-average molecular weight Mwc of the carboxyl-containing vinylidene fluoride copolymer absorbing light at a wavelength of 345 nm is determined, the Mwc is less than 0.90 relative to the Mwa.
[0013] [2] The present invention provides the electrode mixture described in [1], wherein the Mwc is 0.25 or more relative to the Mwa.
[0014] [3] The present invention provides the electrode mixture described in [1] or [2], wherein the average particle size of the electrode active material is less than 15 μm.
[0015] [4] The present invention provides an electrode mixture according to any one of [1] to [3], wherein the carbon coating of the electrode active material is less than 2.5% by mass.
[0016] [5] The present invention provides the electrode mixtures described in [1] to [4], wherein the vinyl compound is a compound represented by the following general formula (1).
[0017] [Chemical Formula 1]
[0018]
[0019] (In general formula (1), R) 1 R 2 R 3 Each can independently represent a hydrogen atom, a halogen atom, or an alkyl group with 1 to 5 carbon atoms; X represents a hydroxyl group or -Y-COOH (where Y represents a radical).
[0020] [6] The present invention provides an electrode compound according to any one of [1] to [4], wherein the vinyl compound is a compound represented by the following general formula (1).
[0021] [Chemical Formula 2]
[0022]
[0023] (In general formula (1), R) 1 R 2 R 3 Each of these can independently represent a hydrogen atom, a halogen atom, or an alkyl group with 1 or more but less than 5 carbon atoms. X represents a hydroxyl group or -Y-COOH (where Y represents a divalent group containing either an oxygen atom or a nitrogen atom, with 1 or more but less than 10 atoms in the main chain, and a molecular weight of 500 or less).
[0024] [7] The present invention provides an electrode comprising the solid component of the electrode mixture described in any one of [1] to [6] above.
[0025] [8] The present invention provides a battery comprising the electrodes described above [7].
[0026] Invention Effects
[0027] According to the present invention, an electrode mixture is provided comprising a carbon-coated electrode active material and a carboxyl-containing vinylidene fluoride copolymer, exhibiting low initial viscosity and good operability. Furthermore, electrodes and batteries obtained using the electrode mixture are also provided. Detailed Implementation
[0028] 1. Electrode mixture
[0029] The electrode mixture of the present invention is a slurry composition comprising a vinylidene fluoride copolymer and a carbon-coated electrode active material (hereinafter also referred to as "active material"), wherein the vinylidene fluoride copolymer has structural units derived from vinylidene fluoride and structural units derived from vinyl compounds having carboxyl groups. The electrode mixture may further comprise conductive additives, solvents, other additives, etc. When the electrode mixture contains a solvent, the vinylidene fluoride copolymer may be dissolved in the solvent or dispersed in the solvent.
[0030] As described above, when preparing electrode mixtures (slurries) by mixing carboxyl-containing vinylidene fluoride copolymers with carbon-coated active materials (such as LFP and LFMP), the viscosity tends to become very high, especially the initial viscosity, and the thixotropy also tends to increase. In this specification, initial viscosity refers to the viscosity of the slurry immediately after stirring. Typically, LFP, LFMP, etc., are small-particle-size, carbon-coated active materials with large surface areas and many functional groups such as OH groups on their surfaces. Therefore, the carboxyl groups of the vinylidene fluoride copolymer readily interact with these functional groups, and when using conventional vinylidene fluoride copolymers, a strong network starting from the active material is formed within the electrode mixture, resulting in thickening. In contrast, the electrode mixture of the present invention, as described above, although containing carboxyl-containing vinylidene fluoride copolymers and carbon-coated electrode active materials, exhibits low initial viscosity and readily achieves good thixotropy. The reasons for this can be summarized as follows.
[0031] The electrode mixture of the present invention contains a vinylidene fluoride copolymer, which is an aggregate of many polymers formed by copolymerizing at least vinylidene fluoride and a vinyl compound having a carboxyl group. The weight-average molecular weight (Mwa) of this vinylidene fluoride copolymer is 50,000 or more. Furthermore, this vinylidene fluoride copolymer comprises: a polymer containing structural units derived from vinylidene fluoride and structural units derived from vinyl compounds (referred to in this specification as a "carboxyl-containing vinylidene fluoride copolymer" or "carboxyl-containing copolymer"); and a polymer mainly composed of structural units derived from vinylidene fluoride and containing no structural units derived from vinyl compounds. Moreover, the weight-average molecular weight (Mwc) of the carboxyl-containing copolymer, determined by the method described later, is less than 0.90 relative to the aforementioned Mwa. That is, relative to the molecular weight distribution of the vinylidene fluoride copolymer, the carboxyl-containing copolymer exists in a relatively low molecular weight region. It can be considered that when the molecular weight of the carboxyl-containing copolymer is relatively small, the carboxyl-containing copolymer does not easily interact with the functional groups on the surface of the active material, and it is not easy to form a strong network; therefore, the viscosity (initial viscosity) of the slurry is not easily increased excessively. The following provides a detailed description of the vinylidene fluoride copolymer contained in the electrode mixture of the present invention, its physical properties, active substances, and other components.
[0032] (vinylidene fluoride copolymer)
[0033] As described above, the vinylidene fluoride copolymer is a copolymer formed by copolymerizing at least vinylidene fluoride with a vinyl compound having a carboxyl group. The amount of structural units derived from vinylidene fluoride in the vinylidene fluoride copolymer is 90.00 mol% or more, preferably 95.00 mol% or more and 99.98 mol% or less, relative to 100.00 mol% of all structural units in the vinylidene fluoride copolymer. When the amount of structural units derived from vinylidene fluoride is 90.0 mol% or more, the physical properties characteristic of vinylidene fluoride are readily obtained. This value can be calculated, for example, by determining the amount of structural units in the vinylidene fluoride copolymer derived from compounds other than vinylidene fluoride.
[0034] On the other hand, the amount of structural units derived from carboxyl-containing vinyl compounds in the aforementioned vinylidene fluoride copolymer is preferably 0.01 mol% or more and 0.80 mol% or less, more preferably 0.02 mol% or more and 0.50 mol% or less, relative to 100.0 mol% of all structural units of the vinylidene fluoride copolymer. When the amount of structural units derived from vinyl compounds is 0.01 mol% or more, the adhesion of the vinylidene fluoride copolymer to the current collector is easily further improved when forming the electrode using the electrode binder. On the other hand, when the amount of structural units derived from vinyl compounds is 0.80 mol% or less, the increase in the initial viscosity of the electrode binder is easily suppressed. The amount of structural units derived from vinyl compounds can be determined by neutralization titration or... 1 The results were obtained from H-NMR spectra, etc.
[0035] Here, the structure of the aforementioned vinyl compound is not particularly limited, as long as it is a compound having a vinyl group capable of polymerizing with vinylidene fluoride and having a carboxyl group. It should be noted that the vinyl compound may contain one or more carboxyl groups. It should also be noted that in this specification, an anhydride structure consisting of two carboxyl groups is also treated as a type of carboxyl group. The vinylidene fluoride copolymer may contain only one structural unit derived from the vinyl compound, or it may contain two or more. Preferred examples of vinyl compounds include compounds represented by the following general formula (1).
[0036] [Chemical Formula 3]
[0037]
[0038] In general formula (1), R 1 R 2 R 3Each of these terms independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 5 carbon atoms. Examples of alkyl groups having 1 to 5 carbon atoms include straight-chain or branched alkyl groups, and specific examples include methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, pentyl, etc. Among these, methyl, ethyl, or butyl are preferred from the viewpoint of ease of acquisition. Furthermore, especially from the viewpoint of minimizing steric hindrance during polymerization with vinylidene fluoride, R... 1 R 2 and R 3 Each is more preferably a hydrogen atom or a methyl group, independently.
[0039] Furthermore, in the above general formula (1), X is a hydroxyl group or a group represented by -Y-COOH. Here, Y represents a radical, Y is preferably a radical containing either an oxygen atom or a nitrogen atom, Y is more preferably a radical containing either an oxygen atom or a nitrogen atom, Y is even more preferably a radical containing either an oxygen atom or a nitrogen atom and having a main chain with 1 or more and 10 or less atoms, Y is preferably a divalent radical containing either an oxygen atom or a nitrogen atom, having a main chain with 1 or more and 10 or less atoms, and a molecular weight of 500 or less.
[0040] The atomic group (Y) can be linear, branched, cyclic, or a combination thereof. From the viewpoint that it is less likely to cause steric hindrance during polymerization with vinylidene fluoride, the atomic group (Y) is preferably linear or branched.
[0041] The main chain of the radical (Y) can have 1 or more and 10 or less, preferably 2 or more and 8 or less. In this specification, the main chain of the radical (Y) refers to the longest chain connecting the carbonyl group of general formula (1) and the carboxyl group of -Y-COOH.
[0042] Here, the aforementioned atomic group (Y) contains either or both of oxygen and nitrogen atoms (hereinafter, they are also collectively referred to as "heteroatoms"). The number of heteroatoms in the atomic group (Y) is preferably 1 or more and 10 or less, more preferably 1 or more and 5 or less. When the atomic group (Y) contains two or more heteroatoms, they can be of the same type or different types. Heteroatoms can be contained in any structure (functional group) and can exist at any position within the atomic group (Y). Examples of structures (functional groups) containing these heteroatoms include ether bonds, ester bonds, carbonyl groups, carboxyl groups, amide groups, hydroxyl groups, etc. Among these, ether bonds, ester groups, carbonyl groups, carboxyl groups, amide groups, and hydroxyl groups are preferred.
[0043] The structure of the atomic group (Y) is not particularly limited. For example, it can be a structure formed by bonding a hydrocarbon group such as alkylene or alkyl with a structure (functional group) containing the aforementioned heteroatoms. It should be noted that the molecular weight of the atomic group (Y) only needs to be below 500, and from the point of view of polymerization reactivity, it is preferably above 30 and below 200.
[0044] Specific examples of compounds represented by the above general formula (1) include: (meth)acrylic acid, (meth)acryloyloxyethyl succinic acid, (meth)acryloyloxypropyl succinic acid, 2-carboxyethyl (meth)acrylate, 2-carboxymethyl (meth)acrylate, (meth)acryloyloxyethyl phthalic acid, N-carboxyethyl (meth)acrylamide, and other (meth)acrylamide compounds. It should be noted that in this specification, (meth)acrylic acid refers to methacrylic acid, acrylic acid, or mixtures thereof; (meth)acrylate refers to methacrylate, acrylate, or mixtures thereof; and (meth)acryloyl group refers to methacryloyl group, acryloyl group, or mixtures thereof.
[0045] From the viewpoints of ease of acquisition and reactivity with vinylidene fluoride, the compounds represented by the above general formula (1) are more preferably acrylic acid, acryloyloxyethyl succinic acid, acryloyloxypropyl succinic acid, 2-carboxyethyl acrylate, and 2-carboxymethyl acrylate.
[0046] The vinyl compounds with carboxyl groups mentioned above are not limited to compounds represented by general formula (1). Examples of vinyl compounds other than those represented by general formula (1) include: unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid; unsaturated dicarboxylic acid anhydrides such as maleic anhydride and itaconic anhydride; and unsaturated dicarboxylic acid monoesters such as monomethyl fumarate, monoethyl fumarate, monomethyl maleate, monoethyl maleate, monomethyl citrate, monoethyl citrate, monomethyl phthalate, monoethyl phthalate, monomethyl itaconic acid, and monoethyl itaconic acid.
[0047] Furthermore, without impairing the purpose and effects of the present invention, the vinylidene fluoride copolymer may also contain structural units derived from compounds other than vinylidene fluoride and the aforementioned vinyl compounds (other compounds). The vinylidene fluoride copolymer may contain only one type of structural unit derived from other compounds, or it may contain two or more types. The total amount of structural units derived from other compounds relative to 100.0 mol% of all structural units of the vinylidene fluoride copolymer is preferably 10.0 mol% or less, more preferably 5.0 mol% or less. These amounts are determined according to… 19 F-NMR spectrum and 1 It is determined by ¹H-NMR spectroscopy, neutralization titration, etc.
[0048] Other examples of compounds include fluorinated vinyl compounds that contain a vinyl group, a fluorine atom, or a fluorinated alkyl group in one molecule. Examples of fluorinated vinyl compounds include: fluoroethylene; trifluoroethylene; tetrafluoroethylene; trifluorochloroethylene; hexafluoropropylene; and perfluoroalkyl vinyl ethers, represented by perfluoromethyl vinyl ethers. Furthermore, other examples of compounds include compounds that contain vinyl groups but do not contain fluorine. Examples include unsaturated hydrocarbon compounds such as ethylene and propylene.
[0049] Here, the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer is only required to be 50,000 or more, preferably 200,000 or more and 4,000,000 or less, and more preferably 250,000 or more and 3,000,000 or less. When the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer is 50,000 or more, the heat resistance and strength of the electrode (electrode mixture layer) obtained using the electrode binder tend to be good. In this specification, the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer is a polystyrene equivalent value determined by gel permeation chromatography (GPC). In this case, the eluent is N,N-dimethylacetamide, and the weight-average molecular weight is determined by a differential refractive index (RI) detector. Mwa is the average of three measurements.
[0050] On the other hand, the weight-average molecular weight (Mwc) of the carboxyl-containing copolymer in the vinylidene fluoride copolymer is less than 0.90 relative to the weight-average molecular weight (Mwa) of the aforementioned vinylidene fluoride copolymer, i.e., Mwc / Mwa < 0.90. Preferably, Mwc / Mwa is 0.25 or more and less than 0.90, more preferably 0.25 or more and less than 0.85, more preferably 0.30 or more and less than 0.70, more preferably 0.30 or more and less than 0.60, and even more preferably 0.30 or more and less than 0.50. As described above, when this ratio is less than 0.90, the initial viscosity of the electrode mixture is less likely to become excessively high.
[0051] Here, the specific weight-average molecular weight (Mwc) of the carboxyl-containing copolymer is preferably 10,000 or more, more preferably 25,000 or more and 4,700,000 or less, even more preferably 50,000 or more and 3,800,000 or less, and particularly preferably 63,000 or more and 2,800,000 or less. When the weight-average molecular weight (Mwc) of the carboxyl-containing copolymer is within this range, the above ratio (Mwc / Mwa) easily falls within the desired range.
[0052] In this specification, the weight-average molecular weight (Mwc) of the carboxyl-containing copolymers described above is a value determined by the following method: A vinylidene fluoride copolymer was mixed with a labeling substance (1-bromomethylpyrene) for labeling carboxyl groups and potassium carbonate, and the carboxyl groups were esterified to obtain a pyrene-modified vinylidene fluoride copolymer. Then, the polystyrene equivalent value was determined using a UV-Vis detector (detection wavelength 345 nm) with N,N-dimethylacetamide as the eluent. It should be noted that the pyrene structure exhibits characteristic absorption in the UV-Vis region, strongly absorbing light at a wavelength of 345 nm. That is, the polymeric average molecular weight (Mwc) of the carboxyl-containing copolymer was determined by esterifying the carboxyl groups with 1-bromomethylpyrene. Mwc is the average of three measurements.
[0053] Here, the specific logarithmic viscosity of the aforementioned vinylidene fluoride copolymer is preferably 0.5 dL / g or more and 6.0 dL / g or less, more preferably 0.5 dL / g or more and 5.0 dL / g or less, and even more preferably 0.8 dL / g or more and 4.5 dL / g or less. When the specific logarithmic viscosity is 0.5 dL / g or more, the adhesion strength of the vinylidene fluoride copolymer to active materials and current collectors is easily improved. On the other hand, when the specific logarithmic viscosity is 5.0 dL / g or less, the initial viscosity of the electrode mixture is not too high, and it is particularly easy to have excellent workability. Specific logarithmic viscosity (η) i The value () represents the logarithmic viscosity. First, 80 mg of vinylidene fluoride copolymer was dissolved in 20 ml of N,N-dimethylformamide, and the viscosity was measured using an Ubbelohde viscometer in a constant temperature bath at 30°C. Then, based on the obtained value, the viscosity was calculated using the following formula.
[0054] η i =(1 / C)・ln(η / η0)
[0055] In the above formula, η is the viscosity of the solution, η0 is the viscosity of N,N-dimethylformamide alone as a solvent, and C is the concentration of vinylidene fluoride copolymer in the solution, i.e., 0.4 g / dl.
[0056] The amount of vinylidene fluoride copolymer contained in the solid component of the electrode mixture (the component after removing volatile components during mixture layer formation) is preferably 0.2% by mass or more and 20% by mass or less, more preferably 0.2% by mass or more and 10% by mass or less, and even more preferably 0.2% by mass or more and 5% by mass or less. When the amount of vinylidene fluoride copolymer is within this range, a high-strength mixture layer is easily obtained.
[0057] The aforementioned vinylidene fluoride copolymers can be prepared by copolymerizing vinylidene fluoride, the aforementioned carboxyl-containing vinyl compounds, and other compounds as needed. Examples of methods for copolymerizing these include suspension polymerization, emulsion polymerization, solution polymerization, etc., with suspension polymerization being preferred from the viewpoint of reducing impurities.
[0058] In suspension polymerization using water as the dispersion medium, suspending agents such as methylcellulose, propoxylated methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, polyvinyl alcohol, polyethylene oxide, and gelatin are added in the range of 0.005 to 1.0 parts by weight, preferably 0.01 to 0.4 parts by weight, relative to 100 parts by weight of all monomers used in copolymerization (vinylidene fluoride, vinyl compounds with carboxyl groups, and other monomers).
[0059] As polymerization initiators, diisopropyl peroxide, di-n-propyl peroxide, di-n-heptafluoropropyl peroxide, isobutyryl peroxide, bis(chlorofluoroyl) peroxide, bis(perfluoroyl) peroxide, tert-butyl peroxypentanoate, etc., can be used. When all monomers used for copolymerization (vinylidene fluoride, vinyl compounds with carboxyl groups, and other monomers as needed) are set to 100 parts by mass, the amount used is 0.05 to 10 parts by mass, preferably 0.15 to 5 parts by mass.
[0060] In addition, chain transfer agents such as ethyl acetate, methyl acetate, diethyl carbonate, acetone, ethanol, n-propanol, acetaldehyde, propionaldehyde, ethyl propionate, and carbon tetrachloride can be added to adjust the degree of polymerization of the obtained vinylidene fluoride copolymer. When using chain transfer agents, if all monomers used for copolymerization (vinylidene fluoride, vinyl compounds with carboxyl groups, and any other monomers) are set to 100 parts by mass, the amount used is usually 0.01 to 5 parts by mass, preferably 0.01 to 3 parts by mass.
[0061] In addition, the total amount of all monomers used in the copolymerization (vinylidene fluoride, vinyl compounds with carboxyl groups, and other monomers) is typically 1:1 to 1:10, preferably 1:2 to 1:5, based on the total monomer:water mass ratio.
[0062] The polymerization temperature T is based on the 10-hour half-life temperature T of the polymerization initiator. 10 Appropriate selection, usually in T 10 -25℃≤T≤T 10 The range of +25℃ is selected. For example, the T range of tert-butyl peroxypentanoate and diisopropyl peroxydicarbonate. 10 The temperatures are 54.6℃ and 40.5℃ respectively (refer to the Nippon Oil Company product catalog). Therefore, in polymerizations using tert-butyl peroxypentanoate and diisopropyl peroxydicarbonate as polymerization initiators, the polymerization temperatures T are appropriately selected within the ranges of 29.6℃≤T≤79.6℃ and 15.5℃≤T≤65.5℃, respectively. There are no particular limitations on the polymerization time, but considering factors such as productivity, it is preferably less than 100 hours. The polymerization pressure is usually applied under pressure, preferably 2.0~10.0 MPa-G.
[0063] Here, as a method to make the weight-average molecular weight (Mwc) of the aforementioned carboxyl-containing copolymer less than 0.90 relative to the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer, the following two methods can be listed as examples. However, these methods are not limited to any particular method. The first method involves mixing vinylidene fluoride (and other compounds) with a complete amount of a carboxyl-containing vinyl compound and then initiating polymerization. The second method involves polymerizing vinylidene fluoride (and other compounds) to a certain extent, then adding a complete amount of a carboxyl-containing vinyl compound to the reaction system within a short time (e.g., within 2 hours) and further polymerizing. This allows the weight-average molecular weight (Mwc) to be within a desired range. Furthermore, the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer can be adjusted by the polymerization initiation dose, chain transfer dose, polymerization temperature, etc.
[0064] (Active substances)
[0065] The electrode mixture of the present invention contains an active substance that is carbon-coated, and the amount of carbon coating relative to the active substance is 0.5% by mass or more and 3.0% by mass or less. The amount of carbon coating is determined by dissolving each positive electrode material in aqua regia by heating, filtering with a membrane filter, and calculating the acid-insoluble component (carbon content) based on the residue on the filter. This amount of carbon coating is preferably 0.5% by mass or more and 2.7% by mass or less, more preferably 0.5% by mass or more and 2.5% by mass or less.
[0066] Here, as long as the above-mentioned carbon coating amount is met, there is no particular restriction on the type of active material. However, generally speaking, in olivine-type lithium compounds such as LiFePO4 (LFP) and LiFeMnPO4 (LFMP), which are used as positive electrode active materials, the surface is mostly coated with carbon to reduce particle resistance, making it easy to meet the above-mentioned coating rate. As mentioned above, when the carbon-coated active material is mixed with a common vinylidene fluoride copolymer having carboxyl groups to prepare an electrode mixture, the initial viscosity tends to increase. In contrast, by combining it with the above-mentioned vinylidene fluoride copolymer, the initial viscosity of the electrode mixture is less likely to increase.
[0067] Furthermore, the average particle size of the aforementioned LFP and LFMP is relatively small. When the average particle size of the active material in the electrode mixture is small, the initial viscosity of the electrode mixture is usually prone to increase. However, in the electrode mixture of the present invention, the aforementioned vinylidene fluoride copolymer does not easily form a robust network structure starting from the active material. Therefore, even though the average particle size of LFP and LFMP is small, the initial viscosity of the electrode mixture is not easily increased. The average particle size of the active material is the particle size at which the particle size accumulation rate is 50% in the volume-based particle size accumulation curve (according to JISK 1474). The average particle size Dv50 of the active material can be 15 μm or less, for example, it can be 0.1 μm or more and 15 μm or less. However, the average particle size of the active material is not limited to this range.
[0068] The amount of active material contained in the electrode mixture is appropriately selected according to the intended use of the electrode mixture, but it is preferably 50% by mass or more and 99.9% by mass or less relative to the total amount of solid components in the electrode mixture. When the amount of active material is within this range, for example, sufficient charge and discharge capacity can be obtained, and the battery performance tends to be good.
[0069] (Conductive additive)
[0070] The electrode mixture may further include conductive additives. There are no particular limitations on the conductive additives contained in the electrode mixture, as long as they are compounds capable of further improving the conductivity between the active materials or between the active materials and the current collector. Examples of conductive additives include acetylene black, Ketjen black, carbon black, graphite powder, carbon nanofibers, carbon nanotubes, and carbon fibers.
[0071] The amount of conductive additive contained in the electrode mixture is appropriately selected according to its type, etc. From the viewpoint of simultaneously improving conductivity and dispersibility of conductive additive, the total amount of solid components in the electrode mixture is preferably 0.1% by mass and 15% by mass or less, more preferably 0.1% by mass or more and 7% by mass or less, and even more preferably 0.1% by mass or more and 5% by mass or less.
[0072] (solvent)
[0073] Electrode mixtures may also contain solvents. Solvents can be non-aqueous solvents or water. Furthermore, non-aqueous solvents can also be polar solvents. Examples of such polar solvents include: amide compounds such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; alcohol compounds such as methanol, ethanol, isopropanol, 2-ethyl-1-hexanol, 1-nonanol, lauryl alcohol, and tripropylene glycol; amine compounds such as o-toluidine, m-toluidine, and p-toluidine; imide compounds such as 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; lactone compounds such as γ-butyrolactone and δ-butyrolactone; sulfoxide / sulfone compounds such as dimethyl sulfoxide and sulfolane; ether compounds such as tetrahydrofuran, diethyl ether, 1,4-dioxane, and diethylene glycol dimethyl ether; and ketone compounds such as acetone, 2-butanone, methyl isobutyl ketone, and cyclohexanone. The electrode mixture may contain only one of the above-mentioned solvents, or it may contain two or more of them.
[0074] There is no particular limitation on the total amount of solvent in the electrode mixture, but it is generally preferred to be 10 parts by mass or more and 150 parts by mass or less relative to 100 parts by mass of the active material.
[0075] (Other ingredients)
[0076] The electrode mixture may also contain dispersants, adhesive aids, thickeners, etc., which can be known compounds. Examples of dispersants include: polyvinylpyrrolidone, methylcellulose, methoxylated methylcellulose, propoxylated methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, polyvinyl alcohol, polyethylene oxide, polypropylene oxide, gelatin, etc. Examples of adhesive aids include: poly(meth)acrylic acid, sodium poly(meth)acrylic acid and other metal salts of poly(meth)acrylic acid, carboxymethyl cellulose, etc. Their amounts are not particularly limited as long as they do not impair the purpose and effect of the present invention, but are preferably 15% by mass or less relative to the total amount of solid components in the electrode mixture.
[0077] Furthermore, the electrode mixture may further include: phosphorus compounds; sulfur compounds; nitrogen compounds such as amine compounds and ammonium compounds; organic acids; organic esters; various silane-based, titanium-based, and aluminum-based coupling agents; and additives such as vinylidene fluoride polymers other than the aforementioned vinylidene fluoride copolymers, polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyacrylonitrile (PAN). These additives are not particularly limited as long as they do not impair the purpose and effects of the present invention, but are preferably 15% by mass or less relative to the total amount of solid components in the electrode mixture.
[0078] (Physical properties of electrode mixture)
[0079] The viscosity of the electrode mixture is not particularly limited as long as it meets the following criteria: a viscosity sufficient to prevent liquid dripping, uneven application, and delayed drying during the formation of the mixture layer; and good workability and coatability during mixture layer preparation. The viscosity of the electrode mixture is measured using an E-type viscometer at 25°C, specifically after a 60-second holding period at 25°C, with a shear rate of 1 second. -1 The value measured 120 seconds after the rotor starts rotating is preferably 2000 mPa·s or more and 60000 mPa·s or less, more preferably 5000 mPa·s or more and 30000 mPa·s or less. When the initial viscosity is within this range, the workability of forming the mixture layer becomes easier.
[0080] In addition, after a 60-second heat treatment period at 25°C using an E-type viscometer, the sample was subjected to a shear rate of 40 seconds. -1 The value measured 30 seconds after the rotor begins to rotate is preferably 1000 mPa·s or more and 5000 mPa·s or less, more preferably 1000 mPa·s or more and 4000 mPa·s or less. Furthermore, at a shearing rate of 40 s... -1 The determined viscosity and the shear rate at 1s -1 The determined viscosity ratio, i.e. (at a shear rate of 1s) -1 Determined viscosity / at a shear rate of 40s -1 The viscosity (of a given value) is preferably 2 or more and 12 or less, more preferably 3 or more and 11 or less. When the above ratio is within this range, the operability of the electrode mixture when forming the mixture layer becomes easier and better.
[0081] (Preparation method of electrode mixture)
[0082] The above-mentioned electrode mixture can be prepared by mixing all the components at once, or by mixing a portion of the components first and then mixing the remaining components.
[0083] 2. Electrodes
[0084] The electrode mixture described above can be used to form the electrode mixture layer of various non-aqueous electrolyte secondary batteries. The electrode of a non-aqueous electrolyte secondary battery, for example, includes a current collector and an mixture layer disposed on the current collector. The electrode mixture described above can be used in the formation of this mixture layer.
[0085] • Current collector
[0086] A current collector is a terminal used to extract electricity. There are no particular limitations on the material used for a current collector; it can be made of metal foil or mesh such as aluminum, copper, iron, stainless steel, steel, nickel, or titanium, or a material with a layer containing carbon black formed on its surface. Alternatively, it can be a material formed by forming a layer containing carbon black on the surface of other media, or a material with the aforementioned metal foil or mesh applied.
[0087] • Mixture layer
[0088] The flux layer is formed by applying the aforementioned electrode flux onto the current collector and allowing it to cure. Specifically, the flux layer contains at least the aforementioned vinylidene fluoride compound and an active substance. The flux layer may be formed on only one side of the current collector or on both sides.
[0089] The additive layer contains at least the components of the electrode additive described above, namely vinylidene fluoride copolymer and active substances, and may further contain conductive additives, dispersants, binders, thickeners, and other additives as needed. These may be the same as those described in the electrode additive.
[0090] The thickness of the agent layer is not particularly limited here; in one example, it is preferably 1 μm or more and 300 μm or less. Furthermore, the weight per unit area of the agent layer formed on one surface of the current collector is not particularly limited and can be any weight per unit area; in one example, it is preferably 50 g / m². 2 Above and 500g / m 2 The following is more preferably 100g / m 2 Above and 300g / m 2 the following.
[0091] The aforementioned mixture layer can be formed by performing a process of applying the aforementioned electrode mixture onto the current collector and then curing it.
[0092] There are no particular limitations on the coating method of the electrode mixture. It can be applied by methods such as doctor blade coating, reverse roller coating, comma bar coating, gravure printing, air knife coating, mold coating, and dip coating.
[0093] Furthermore, after coating the electrode mixture, the solvent is dried by heating at any temperature. In one example, the drying temperature is preferably 60°C or higher and 200°C or lower, more preferably 80°C or higher and 150°C or lower. Heating can be performed multiple times at different temperatures. It should be noted that the solvent in the mixture can be dried under atmospheric pressure, under pressure, or under reduced pressure, or in an environment with air, nitrogen, argon, etc. Further heat treatment can be performed after drying.
[0094] After the electrode mixture is coated and dried, it can be further pressed. Pressing increases the electrode density. In one example, the pressing pressure is preferably 1 kPa or more and 10 GPa or less.
[0095] 3. Battery
[0096] As described above, the electrode mixture can be used in the electrodes of various non-aqueous electrolyte secondary batteries, but it can also be used to form other layers in non-aqueous electrolyte secondary batteries.
[0097] Example
[0098] Hereinafter, specific embodiments and comparative examples of the present invention will be described together, but the present invention is not limited thereto.
[0099] 1. Methods for determining and evaluating various physical properties
[0100] The specific concentration logarithmic viscosity, weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer, and weight-average molecular weight (Mwc) of the carboxyl-containing copolymer are shown below. The methods for determining the average particle size (Dv50) and carbon coating of the electrode active material are shown below.
[0101] Furthermore, the method for determining the viscosity of the electrode mixture slurry is as follows.
[0102] (1) Specific concentration logarithmic viscosity of vinylidene fluoride copolymer
[0103] The specific logarithmic viscosity of the vinylidene fluoride copolymer was determined as follows. First, 80 mg of the vinylidene fluoride copolymer was dissolved in 20 ml of N,N-dimethylformamide, and the viscosity was measured using an Ubbelohde viscometer in a constant temperature bath at 30°C. Then, based on the obtained value, the specific logarithmic viscosity (η) of the vinylidene fluoride copolymer was calculated using the following formula. i ).
[0104] η i =(1 / C)・ln(η / η0)
[0105] In the above formula, η is the solution viscosity, η0 is the viscosity of N,N-dimethylformamide alone as a solvent, and C is the concentration of vinylidene fluoride polymer in the solution, i.e., 0.4 g / dl.
[0106] (2) Weight-average molecular weight Mwa of vinylidene fluoride copolymer
[0107] The weight-average molecular weight Mw1 of the vinylidene fluoride copolymers prepared in the examples and comparative examples was determined using a differential refractometer (RI). Specifically, GPC (gel permeation assay) was performed under the following conditions, and Mwa was determined using a differential refractometer. This operation was performed three times, and the average value was taken as Mwa.
[0108] Separation columns: Shodex KD-807, KD-806M.
[0109] Detector: RI-4030 (differential refractive index detector) manufactured by Japan Spectrophotometer Co., Ltd.
[0110] Eluent: 10 mM LiBr-N,N-dimethylacetamide (DMAc) solution.
[0111] Eluent flow rate: 0.5 mL / min.
[0112] Column temperature: 40℃.
[0113] The standard polymer used for the standard curve is TSK standard POLY (STYRENE) (manufactured by Tosoh Corporation).
[0114] (3) Weight-average molecular weight Mwc of carboxyl-containing copolymers
[0115] 10 mg of the vinylidene fluoride copolymer prepared in each example and comparative example, 2 mg of 1-bromomethylpyrene, and 2 mg of potassium carbonate were added to 10 mg of DMAc. The mixture was dissolved and reacted in a constant-temperature shaking bath at 50°C with stirring. The potassium carbonate was removed using a 0.45 μm filter. Thus, the carboxyl groups of the carboxyl-containing copolymer in the vinylidene fluoride copolymer were labeled with 1-bromomethylpyrene.
[0116] The weight-average molecular weight (Mwc) of the carboxyl-containing copolymer (polymer absorbing light at a wavelength of 345 nm) in the 1-bromomethylpyrene-labeled vinylidene fluoride copolymer was determined using a UV-Vis detector. The determination was performed under the same conditions as described above for Mwc, except for the detector. The detection wavelength was set to 345 nm, and the weight-average molecular weight (Mwc) of the carboxyl-containing copolymer was calculated. This was performed three times, and the average value was taken as Mwc.
[0117] (4) Determination of the average particle size Dv50 of the electrode active material
[0118] To each electrode active material, add 0.1 g of dispersant (cationic surfactant "SN-WET366" (manufactured by San Nopco)) to the sample to allow the dispersant to fuse with the sample. Next, add 20 mL of pure water and disperse using an ultrasonic cleaner for approximately 5 minutes. Then, use a particle size distribution measuring device (Microtrac MT3300EXII) to determine the particle size distribution within the range of 0.1–1000 μm. Note that the dispersion medium was pure water with a refractive index of 1.333. Based on the obtained particle size distribution, calculate the particle size at which the cumulative frequency is 50% of the volume, and determine the average particle size Dv50.
[0119] (5) Method for determining the carbon coating amount of electrode active material
[0120] Weigh 500 mg of each electrode active material into a beaker, add 40 mL of water and aqua regia (3 mL nitric acid + 9 mL hydrochloric acid), heat to dissolve, filter through a membrane filter, and calculate the acid-insoluble component (carbon coating amount) based on the residual amount.
[0121] (6) Viscosity of electrode mixture slurry
[0122] The viscosity of the electrode mixtures prepared in the examples and comparative examples was measured. The electrode mixtures were prepared by placing them immediately into an E-type viscometer (Toki Sangyo Co., Ltd. RE-215 type viscometer, rotor 3°×R14). After being held at 25°C for 60 seconds in the apparatus, the viscosity was measured at a shear rate of 1 second. -1 Rotate the rotor, and determine the viscosity of the slurry 120 seconds after the rotor starts rotating.
[0123] Furthermore, within the aforementioned device, after a 60-second heat preservation period at 25°C, a shearing rate of 40 seconds is applied. -1 Rotate the rotor, and determine the viscosity of the slurry 30 seconds after the rotor starts rotating.
[0124] Furthermore, the determined shear rate 1s was determined. -1 The slurry viscosity and shear rate 40s -1 The viscosity ratio between the slurry viscosities (shear speed 1s) -1 Slurry viscosity / shear rate 40s -1 (the viscosity of the slurry).
[0125] 2. Preparation of materials
[0126] The following materials were prepared as materials for the electrode mixtures prepared in the examples and comparative examples.
[0127] (1) Active substances
[0128] • LFP-A carbon coating: 1.0%, average particle size D50: 2μm)
[0129] • LFP-B carbon coating: 1.4%, average particle size D50: 4μm)
[0130] • LFP-C carbon coating: 2.1%, average particle size D50: 10μm)
[0131] • LFMP, carbon coating: 2.0%, average particle size D50: 1 μm)
[0132] • LCO carbon coating: 0.0%, average particle size D50: 2μm)
[0133] (2) Vinylidene fluoride copolymer
[0134] • VDF / APS-1: Prepared in Synthesis Example 1 below
[0135] • VDF / APS-2: Prepared in the following synthesis example 2
[0136] • VDF / AA-1: Prepared in Synthesis Example 3 below
[0137] • VDF / AA-2: Prepared in Synthesis Example 4 below
[0138] <Synthesis example 1>
[0139] In a 2-liter autoclave, 1240 g of ion-exchanged water was added as a dispersion medium, 0.4 g of Metrolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.) as a cellulose-based suspending agent, 2.0 g of acryloyloxypropyl succinic acid (APS), 1.40 g of a 50 wt% diisopropyl peroxide dicarbonate-HFE-347pc-f polymerization initiator solution, 0.8 g of ethyl acetate as a chain transfer agent, and 400 g of vinylidene fluoride. The mixture was heated to 45°C over 2 hours. While maintaining the temperature at 45°C, the reaction continued until the pressure in the system decreased to 1.5 MPa.
[0140] After polymerization, the polymer slurry was heat-treated at 95°C for 60 minutes, then dehydrated, washed with water, and subsequently dried at 80°C for 20 hours to obtain a copolymer of vinylidene fluoride (VDF) and acryloyloxypropyl succinic acid (APS), namely, a vinylidene fluoride copolymer (VDF / APS-1) powder. The specific viscosity logarithmic viscosity, weight-average molecular weight Mwa, and weight-average molecular weight Mwc of the carboxyl-containing copolymers contained in this vinylidene fluoride copolymer are shown in Table 1 below.
[0141] <Synthesis example 2>
[0142] To a 2-liter autoclave, 1054.5 g of ion-exchanged water as a dispersion medium, 0.23 g of Metrolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.) as a cellulose-based suspending agent, 0.07 g of APS, 3.50 g of a 50 wt% diisopropyl peroxide-HFE-347pc-f polymerization initiator solution, and 400 g of vinylidene fluoride were added. The mixture was heated to 26°C over 55 minutes. While maintaining the temperature at 26°C, 0.86 g of a 5 wt% APS aqueous solution was added over a period of 4.3 hours, starting 2 hours after the start of heating. Starting from the point where the pressure decreased by 0.2 MPaG at the end of the heating process, the mixture was heated to 55°C over 40 minutes. While maintaining the temperature at 55°C, the reaction continued until the pressure in the system decreased to 1.3 MPaG.
[0143] The obtained polymer slurry was treated using the same method as in Synthesis Example 1, thereby obtaining a powder of a copolymer of vinylidene fluoride (VDF) and acryloyloxypropylsuccinic acid (APS), namely, a vinylidene fluoride copolymer (VDF / APS-2). The specific viscosity logarithmic viscosity, weight-average molecular weight Mwa, and weight-average molecular weight Mwc of the carboxyl-containing copolymer contained in this vinylidene fluoride copolymer are shown in Table 1 below.
[0144] <Synthesis example 3>
[0145] To a 2-liter autoclave, add 1056 g of ion-exchanged water as a dispersion medium, 0.44 g of Metrolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.) as a cellulose-based suspending agent, 9.37 g of acrylic acid (AA), 5.28 g of a 50 wt% tert-butyl peroxypentyl ester-HFE-347pc-f polymerization initiator solution, 0.44 g of ethyl acetate as a chain transfer agent, and 440 g of vinylidene fluoride. The mixture is heated to 52°C over 110 minutes. While maintaining the temperature at 52°C, the reaction continues until the pressure in the system decreases to 4.7 MPaG.
[0146] The obtained polymer slurry was processed using the same method as in Synthesis Example 1, thereby obtaining a powder of a copolymer of vinylidene fluoride (VDF) and acrylic acid (AA), namely, a vinylidene fluoride copolymer (VDF / AA-1). The specific viscosity logarithmic viscosity, weight-average molecular weight Mwa, and weight-average molecular weight Mwc of the contained carboxyl-containing copolymers of this vinylidene fluoride copolymer are shown in Table 1 below.
[0147] <Synthesis example 4>
[0148] To a 2-liter autoclave, add 1056 g of ion-exchanged water as a dispersion medium, 0.44 g of Metrolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.) as a cellulose-based suspending agent, 0.22 g of acrylic acid (AA), 3.08 g of a 50 wt% tert-butyl peroxypentyl ester-HFE-347pc-f solution as a polymerization initiator, 0.44 g of isododecane as a chain transfer agent, and 440 g of vinylidene fluoride. The mixture is heated to 52°C over 110 minutes. While maintaining the temperature at 52°C, add 3.74 g (1 wt% AA aqueous solution) to maintain the pressure after the heating is complete. Continue the reaction until the pressure in the system drops to 7.18 MPaG.
[0149] The obtained polymer slurry was processed using the same method as in Synthesis Example 1, thereby obtaining a powder of a copolymer of vinylidene fluoride (VDF) and acrylic acid (AA), namely, a vinylidene fluoride copolymer (VDF / AA-2). The specific logarithmic viscosity, weight-average molecular weight Mwa, and weight-average molecular weight Mwc of the contained carboxyl-containing copolymer of this vinylidene fluoride copolymer are shown in Table 1 below.
[0150] (3) Properties of vinylidene fluoride copolymer
[0151] The physical properties of vinylidene fluoride copolymers are shown below.
[0152] [Table 1]
[0153]
[0154] 3. Preparation of electrode mixture
[0155] The electrode mixtures were prepared using the following methods.
[0156] (Example 1)
[0157] LFP-A was used as the electrode active material, VDF / APS-1 as the vinylidene fluoride copolymer (binder), and a carbon nanotube (CNT) NMP dispersion as the conductive additive. These were then mixed using a planetary rotary mixer, manufactured by Celgene Corporation, Awatori Rentaro ARE310, to prepare the electrode mixture. The resulting electrode mixture had a mass ratio of electrode active material, conductive additive, and binder of 100:2:2.5, and a solids concentration of 55.0% by mass. The viscosity of the slurry at this point is shown in Table 2.
[0158] (Examples 2-5, Comparative Examples 1-5, and Reference Examples 1 and 2)
[0159] As shown in Table 2, the electrode mixture was prepared in the same manner as in Example 1, except that the type of electrode active material, the type of vinylidene fluoride copolymer, and the concentration of solid components in Example 4 and Comparative Example 4 were changed to 52%.
[0160] (result)
[0161] [Table 2]
[0162]
[0163] As shown in Table 2 above, when using uncoated active materials, there was no significant difference depending on the type of carboxyl-vinylidene fluoride copolymer (Reference Example 1 and Reference Example 2). In contrast, when comparing Example 1 and Comparative Example 2, even when using the same active material, the slurry viscosity (especially at shear rates s) varied depending on the Mwc / Mwa ratio described above. -1 There are significant differences in viscosity (under certain conditions), resulting in significant differences in viscosity ratio. The same applies to the comparison between Examples 2-5 and Comparative Examples 2-5. Furthermore, when the weight-average molecular weight Mwa of the vinylidene fluoride copolymer is 50,000 or more, and the weight-average molecular weight Mwc of the carboxyl-containing copolymer is less than 0.90 relative to Mwa, the slurry viscosity (especially the shear rate s) is significantly different. -1 The viscosity was 51041 mPa·s or less, and the viscosity ratio was also 11.2 or less (Examples 1-5). That is to say, there was no significant difference from Reference Example 1 and Reference Example 2.
[0164] This application claims priority based on Japanese Patent Application No. 2024-056545, filed on March 29, 2024. The entire contents of that application are incorporated herein by reference.
[0165] Industrial availability
[0166] According to the present invention, an electrode mixture is provided comprising a carbon-coated electrode active material and a carboxyl-containing vinylidene fluoride copolymer, exhibiting low initial viscosity and good operability. This electrode mixture is highly useful in the manufacture of various batteries.
Claims
1. An electrode mixture comprising: A vinylidene fluoride copolymer having structural units derived from vinylidene fluoride and structural units derived from vinyl compounds having carboxyl groups; and Carbon-coated electrode active material The carbon coating amount of the electrode active material is 0.5% by mass or more and 3.0% by mass or less relative to the mass of the electrode active material. The weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer is above 50,000. When the vinylidene fluoride copolymer is modified with a labeling substance composed of 2-bromomethylpyrene, the weight-average molecular weight (Mwc) of the carboxyl-containing vinylidene fluoride copolymer that absorbs light at a wavelength of 345 nm is determined. The Mwc is less than 0.90 relative to the Mwa.
2. The electrode mixture according to claim 1, wherein, The Mwc is greater than or equal to the Mwa.
3. The electrode mixture according to claim 1, wherein, The average particle size of the electrode active material is less than 15 μm.
4. The electrode mixture according to claim 1, wherein, The carbon coating of the electrode active material is less than 2.5% by mass.
5. The electrode mixture according to claim 1, wherein, The vinyl compound is a compound represented by the following general formula (1), [Chemical Formula 1] In general formula (1), R 1 R 2 R 3 Each can independently represent an alkyl group having 1 or more but less than 5 hydrogen atoms, halogen atoms, or carbon atoms. X represents a hydroxyl group or -Y-COOH, and Y represents a radical.
6. The electrode mixture according to claim 1, wherein, The vinyl compound is a compound represented by the following general formula (1), [Chemical Formula 1] In general formula (1), R 1 R 2 R 3 Each can independently represent an alkyl group having 1 or more but less than 5 hydrogen atoms, halogen atoms, or carbon atoms. X represents a hydroxyl group or -Y-COOH, and Y represents a divalent group containing either an oxygen atom or a nitrogen atom, with a main chain having 1 or more but less than 10 atoms and a molecular weight of less than 500.
7. An electrode comprising the solid component of the electrode mixture according to any one of claims 1 to 6.
8. A battery comprising the electrode according to claim 7.
Citation Information
Patent Citations
Composite logarithmic period antenna
JP1982097206A
Vinylidene fluoride-based copolymer
JP1994172452A
Vehicle weight estimation device and attenuation force adjustment type suspension device
JP2024056545A